Rural business establishment and interconnections with natural resources in Halaba, Central Ethiopia - Tesfaye, Y.; Moges, A.; Teshale, T.; Girma, R.; Mekuria, Wolde; Phimister, E.; Smith, J.; Hallet, P. (International Water Management Institute, 2025)
This brief outlines key recommendations from research projects aimed at (i) addressing governance challenges that impede the effective establishment of rural businesses, and (ii) ensuring the sustainable integration of rural businesses with natural resources in Halaba in Ethiopia. The studies were supported by projects such as Local-Level Land Degradation Assessment Towards Sustainable Land Management for Improved Livelihoods in the Ethiopian Rift Valley (SMILE-REDAA) and Reducing land degradation and carbon loss from Ethiopia’s soils to strengthen livelihoods and resilience (RALENTIR). The brief sets the context for rural employment and businesses, going on to discuss the relationship between rural businesses, natural resources, stakeholders, institutional structures, and start-up activities in Halaba. Following this, the challenges and opportunities of establishing rural businesses are explored. Finally, it presents the implications of successful interventions and offers recommendations for policymakers and other stakeholders to effectively establish rural businesses, with a focus on sustainable natural resource management.